Quick Hits for Pediatric Emergency Medicine (Springer International Publishing, 2018)
This book covers essential information necessary in diagnosing and treating pediatric patients in the emergency room. Emergencies require quick and precise decision making that does not allow for extended reading or fact-checking to ensure all factors are considered. This pocket guide addresses that need by placing vital clinical management and algorithms into a quick and simple guidebook that can be accessed within moments from a scrub pocket or white coat. It is an easy, quick access reference that can be used for those facts that are absolutely essential, but are often difficult to remember. Color images and flow charts allow doctors to grasp the essentials quickly, while more detailed explanations are included alongside for trainees. Quick Hits for Pediatric Emergency Medicine uses tips, caveats, drug dosing, and pearls to assist the provider who may not be familiar with all of the unique nuances of the pediatric population. This is ideal for emergency department physicians, nurses, and trainees including students, residents, and fellows.